Exploiting the power of Gamification in Journal club - Bashir, Muhammad Mustehsan; Khan, Rehan Ahmad (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effect of individual versus team competitiongamification on trainees’ engagement in journal club. Methods: The quasi-experimental study was conducted at two tertiary care hospitals in Lahore, Pakistan, from December, 2019 to May, 2020, and comprised all plastic surgery residents in training years 3-5who had attended non-gamified journal club sessions. They were divided into two groups. Initially, two journal club sessions were run in a gamified manner. Group 1had an individual competition whereas group 2 had a team competition. In the second phase, the group orientation was reversed. Engagement scores were measured using the student engagement survey toolat baseline, at the completion of the first part, and at end of the intervention. Data was analysed using SPSS 22. Results: Of the 44 participants, 23(52.3%) were in group 1 and 21(47.7%) in group 2. Overall, there were 27(61%) females and 17(39%) males. The mean age of the sample was 31+/-2 years. Gamification resulted in significant increase in the level of residents’ engagement in journal club activities compared to the baseline scores(p<0.05). There was no significant inter-group difference in the post-intervention engagement scores (p>0.05). Conclusion: Gamification designs used in the journal club activity increased student engagement level compared to the pre-intervention score, but gamification design was not a significant factor in this regard. Key Words: Journal club, Gamification, Game designs, Student engagement. Continue